2019
DOI: 10.1002/advs.201802057
|View full text |Cite
|
Sign up to set email alerts
|

Robust Photodynamic Therapy Using 5‐ALA‐Incorporated Nanocomplexes Cures Metastatic Melanoma through Priming of CD4+CD8+ Double Positive T Cells

Abstract: Advanced melanoma can rarely be cured. Photodynamic therapy (PDT) readily eradicates the primary melanoma but has limited ability to destroy the spreading tumor cells unless supported by other combinative interventions to augment systemic antitumor immunity. Based on the previously synthesized penetration‐enhancing biomaterials, a topically administered nanoformulation is developed, which profoundly assists 5‐aminolevulinic acid (5‐ALA) in circumventing skin barrier to be selectively delivered to tumor cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Skin cancers represent a growing proportion of all human cancers and are associated with high mortality 1 . Although it only accounts for 4% of all skin cancer cases, malignant melanoma is the main cause of death in superficial skin tumors 2 , 3 . Surgery and chemotherapy are the major treatments for malignant melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Skin cancers represent a growing proportion of all human cancers and are associated with high mortality 1 . Although it only accounts for 4% of all skin cancer cases, malignant melanoma is the main cause of death in superficial skin tumors 2 , 3 . Surgery and chemotherapy are the major treatments for malignant melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…ROS are also related to immunogens and tolerogenic processes[ 24 ]. The increased systemic immunity or enhanced tumor immunity induced by PDT may also be mediated by ROS[ 25 ]. Currently, although little is known about whether or how ROS are involved in stem cell immunity, it has been determined that identifying the mechanism by which ROS metabolism affects the fate of stem cells will promote the necessary understanding to apply PDT to inhibit the spread of distant cancer stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although PDT is used to treat superficial malignancies, its immunogenicity has the potential to eliminate systemic CSCs. But in a counterintuitive outcome, some research found that low-dose PDT promotes tumor cells metastasis[ 25 , 26 ]. The epithelial-mesenchymal transition (EMT) has been shown to be one of the causes of cancer cell migration and invasion[ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, not much information about the ALA-PDT induced adaptive immunity is available. A study has shown that memory T cells (CD44 hi CD62L hi ) accumulate in the tumor and spleen of ALA-PDT treated mice [60]. and activation.…”
Section: Pdt and The Adaptive Immune Systemmentioning
confidence: 99%